Strategies to promote equity and inclusion in schools. Documentary study - Mounkoro, Ismaila (2024)
The purpose of this article was to carry out a documentary study about inclusive education. The main and most relevant ideas that will express the existence of diversity in education were selected, and information on strategies for teachers where they can cope with the changes in education that leads to inclusion was recovered. He concludes that it has become an obligation for teachers to create strategies that include educational values. For this, the attitude of the teacher in the classroom is fundamental in this process of educational inclusion, with a series of beliefs and feelings, some of which are sometimes in favor, others against.